DAMPAK PENINGKATAN TARIF IMPOR GULA TERHADAP PENDAPATAN PETANI TEBU - A. HUSNI MALIAN; SAPTANA - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2003)
International sugar price tended to decline during 2002 due to high stock sugar inproducing countries and high import tariff by consumed countries. Such condition resultingnegative impact for sugar cane farmers. Therefore, government increased import tariff to700/kg to increase farmer’s income. Based on some assumptions; price of white sugar cane inthe world US $ 225/ton, value of exchange rate Rp. 8,500 – Rp. 8,700/US $, a range ofrendemen 6.00 – 6.50 % and farmers receive management fee 20 % from BEP; specific tariffrange from Rp 950,- to Rp 1,300/kg. To reduce the negative impact, government providedsubsidized to farmers calculated from BEP + 20% (management fee) subtracted by lelangprice at farmer level.